The Effect of Yoga Interventions on Cancer-Related Fatigue and Quality of Life for Women with Breast Cancer: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (October 2020) - O'Neill, Meagan; Samaroo, Dominic; Lopez, Christian; Tomlinson, George; Santa Mina, Daniel; Sabiston, Catherine; Culos-Reed, Nicole; Alibhai, Shabbir M. H.
Background: Women with breast cancer (BC) are living longer with debilitating side effects such as cancer-related fatigue (CRF) that affect overall well-being. Yoga promotes health, well-being and may be beneficial in reducing CRF. Although there have been previous systematic reviews and meta-analyses, the effects of yoga on CRF and quality of life (QOL) remain unclear, particularly in comparison with other types of physical activity (PA). Our objective is to carry out a systematic review and meta-analysis of the effects of yoga on CRF and QOL in women with BC. Methods: Electronic databases were searched (MEDLINE, Embase Classic+Embase and EMB Reviews, Cochrane Central CT) from inception to May 2018. Randomized controlled trials were included if they were full text, in English, included a yoga intervention, a comparator (including non-PA usual care or alternate PA intervention), and reported on CRF or QOL. Effects of yoga were pooled using standardized mean difference (SMD) via a random effects model. Results: Of the 2468 records retrieved, 24 trials were included; 18 studies compared yoga to a non-PA comparator and 6 to a PA comparator. Yoga demonstrated statistically significant improvements in CRF over non-PA (SMD −0.30 [−0.51; −0.08]) but not PA (SMD −0.17 [−0.50; 0.17]) comparators. Additionally, yoga demonstrated statistically significant improvements in QOL over non-PA (SMD −0.27 [−0.46; −0.07]) but not PA (SMD 0.04 [−0.22; +0.31]) comparators. Discussion: This meta-analysis found that yoga provides small to medium improvements in CRF and QOL compared to non-PA, but not in comparison to other PA interventions.